PERKEMBANGAN IDENTITAS KULTURAL DI PEMUKIMAN BARU PASCA BENCANA DI ACEH : (Studi Pada Lingkungan Sosial Warga Perumahan Jacky Chan, Desa Neuhen, Kabupaten Aceh Besar) - Nurkhalis (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
The effect of tremendous disaster causes the loss and the damage of the primary need (i,e house), in which the regions damaged by the disaster are appointed as disasterprone areas, pushing the government and foreign donors to calculate new resettlement to tsunami victims.It helps them continue their survival. This research uses qualitative research with the theory of Peter Berger and Thomas Luckman which is social constructive. It focuses on how the process of formulation of identity of individual cultural from interaction process among the people at Jacky Chan Resettlement In the process of individual cultural identity formation at Jacky Chan Resettlement, it found that there are 3 kinds of identities; among others are, China-ambon who is affiliated with the merging that gained from primary 'integrated' (the domination still involving primary socialization). And next China-Aceh identity (cultural of Aceh and China are balanced among the individual) and there is compatible identity (this process encounters the process of cultural identity formation change)